Influence of the chemical composition on the ausferritic transformation in carbide-free bainitic cast steel - Basso, Alejandro Daniel (2014)
This work focuses on the study of the solid state transformations that take place during the austempering of high silicon carbide-free bainitic cast steels with different chemical composition. In order to get this objective three cast steel melts with different chemical compositions were produced, evaluating the influence of Cr, Mn, Ni, Al and Co. For each of these steels, samples were subjected to an austempering heat treatment at 340 °C varying the austempering time from 5 sec to 120 sec. The results show that small regions of free ferrite were obtained during continuous cooling from the austenitising to the austempering temperatures in unalloyed high silicon cast steels. At short austempering time (5 sec), the presence of a small fraction of ausferrite was observed. Austempering for 60 sec showed a larger amount of ausferrite. However, the ausferritic reaction is incomplete, and some martensite also was present, mainly located in last to freeze (LTF) zones. After an austempering of 120 sec, a fully ausferritic matrix was obtained. The addition of Cr and Mo avoided the initial precipitation of free ferrite, and lowered the isothermal transformation kinetics. On the other hand the use of Al and Co increase the presence of ferrite formed during continuous cooling and accelerates the kinetics of the ausferritic reaction.